Note on the population structure of Echinocactus platyacanthus (Cactaceae) in the Biosphere Reserve “Barranca de Metztitlán”, Hidalgo, Mexico - Castañeda-Romero, Malinali; Luna-Contreras, Monserrat; Vela-Godinez, Daniel; Montoya-Santiago, Gessel; González-Bermúdez, Alejandro; Martínez Peña, Rodrigo; Esperón-Rodríguez, Manuel (Instituto de Ecología, A.C., 2016)
Echinocactus platyacanthus is one of the most abundant and widely distributed cacti in Mexico. In this work we compared the population structure of this species in two areas with contrasting accessibility degree within the Biosphere Reserve “Barranca de Metztitlán” in the state of Hidalgo. The site with difficult accessibility (S1) had a larger total number of individuals, with larger dimensions, and more juveniles. The site with easy accessibility (S2) had a predominance of adults. A total of 456 individuals were counted and only one sapling was found. We estimated a population density of 1410 individuals/ha in S1 and 863 individuals/ha in S2. We determined the type of population as regressive, because in both sites we found a significantly larger number of individuals in the stage of maturity and a low number of juveniles (12.9%), which suggests a future population decline.